2014
DOI: 10.1016/j.ijpe.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation: A real option to restore value to the biopharmaceutical R&D

Abstract: a b s t r a c tThe pharmaceutical landscape has changed, and new business models, based on alliances, are increasingly being adopted in this industry. Biotechnology advances have pushed this development, and pooling complementary resources coming from incumbents and newcomers is a key skill to succeed: these are the premises for a quick spread of the open innovation (OI) paradigm in this industry. R&D portfolio selection needs R&D project evaluation, and Real Options Analysis (ROA) is acknowledged as a powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 40 publications
0
29
0
2
Order By: Relevance
“…Open innovation and the application of real options frameworks (Copeland & Tufano, 2004;Guthrie, 2009) for the portfolio of R&D Ventures allows businesses to evaluate and compare the risk exposure of a technology development approach with internal or external capabilities and resources, which is supported by the open innovation literature (Lo Nigro et al, 2013). However Dahlander & Gann (2010) found that there is a limited understanding about the cost of openness, the underlying decision process and the elaboration of "…open innovation from the perspective of product/ technology lifecycles and the different phases through which an innovation evolves from conceptualization to commercialization."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open innovation and the application of real options frameworks (Copeland & Tufano, 2004;Guthrie, 2009) for the portfolio of R&D Ventures allows businesses to evaluate and compare the risk exposure of a technology development approach with internal or external capabilities and resources, which is supported by the open innovation literature (Lo Nigro et al, 2013). However Dahlander & Gann (2010) found that there is a limited understanding about the cost of openness, the underlying decision process and the elaboration of "…open innovation from the perspective of product/ technology lifecycles and the different phases through which an innovation evolves from conceptualization to commercialization."…”
Section: Discussionmentioning
confidence: 99%
“…In applying the ROA (Yeo & Qiu, 2002;Copeland & Antikarov, 2001;Leiblein, 2003;Guthrie, 2009) to open innovation, new capabilities are proposed to support the decision between an internal or external R&D project (Vanhaverbeke et al, 2008). In a biopharmaceutical study (Lo Nigro et al,2013) it has been proposed to evaluate R&D projects with ROA for in house development or in an alliance open innovation model. An overview of ROA applications and a model to evaluate R&D projects has been suggested by Perlitz et al (1999) and the value of management flexibility with a discussion of different real options in technology investments has been introduced by Yeo & Qiu (2002).…”
Section: Introductionmentioning
confidence: 99%
“…() and Lo Nigro et al . () take into account OI solutions into their models. In particular, Rogers et al .…”
Section: Portfolio‐selection Literature Overviewmentioning
confidence: 99%
“…R&D portfolio decisions are, mainly, made based on financial indicators, such as NPV or IRR (Ghasemi et al, 2011;Nigro et al, 2014;Vandaele & Decouttere, 2013). However, several studies have shown that the use of traditional financial techniques in project evaluation was not the most suitable for the analysis of investment in R&D (Chan et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%